rhomboid and Star interact synergistically to promote EGFR/MAPK signaling during Drosophila wing vein development. - Guichard, A.; Biehs, B.; Sturtevant, M.A.; Wickline, L.; Chacko, J.; Howard, K.; Bier, E. (Development, 1999)
Genes of the ventrolateral group in Drosophila are dedicated to developmental regulation of Egfr signaling in multiple processes including wing vein development. Among these genes, Egfr encodes the Drosophila EGF-Receptor, spitz (spi) and vein (vn) encode EGF-related ligands, and rhomboid (rho) and Star (S) encode membrane proteins. In this study, we show that rho-mediated hyperactivation of the EGFR/MAPK pathway is required for vein formation throughout late larval and early pupal development. Consistent with this observation, rho activity is necessary and sufficient to activate MAPK in vein primordium during late larval and early pupal stages. Epistasis studies using a dominant negative version of Egfr and a ligand-independent activated form of Egfr suggest that rho acts upstream of the receptor. We show that rho and S function in a common aspect of vein development since loss-of-function clones of rho or S result in nearly identical non-autonomous loss-of-vein phenotypes. Furthermore, mis-expression of rho and S in wild-type and mutant backgrounds reveals that these genes function in a synergistic and co-dependent manner. In contrast, spi does not play an essential role in the wing. These data indicate that rho and S act in concert, but independently of spi, to promote vein development through the EGFR/MAPK signaling pathway.